In vitro anticancer evaluation of enceleamycin A and its underlying - Khan, Abujunaid; Pradeep, S.; Dastager, Syed G. (RSC Advances, 2023)
It has become more crucial than ever to find novel anticancer compounds due to the rise in cancer mortality and resistance to the present chemotherapeutic drugs. Naphthoquinones are regarded as privileged structures for their ability to inhibit various cancers. The current study examined three novel furo-naphthoquinones (Enceleamycins A-C) previously isolated from Amycolatopsis sp. MCC 0218 for their anticancer potential. Enceleamycin A demonstrated considerable cytotoxicity for triple-negative breast cancer (TNBC) MDA-MB-231 cells with an IC50 value of 1.25 mu g mL(-1) (3.78 mu M). It also showed the ability to inhibit MDA-MB-231 cell migration. Enceleamycin A raises intracellular ROS levels in TNBC cells, ultimately leading to apoptotic cell death, as demonstrated by Annexin V/PI staining. The molecular docking and simulation investigation revealed better binding affinity of Enceleamycin A with AKT2, which plays a vital role in breast cancer's invasiveness and chemo-resistance. Enceleamycin A inhibits the AKT2 enzyme in vitro with an IC50 value of 0.736 mu g mL(-1) (2.22 mu M), further validating the docking study. The in silico physicochemical and pharmacokinetics characteristics of Enceleamycin A demonstrated its drug-likeness. Intriguingly, Enceleamycin A is non-hemolytic in nature. Taken together, Enceleamycin A could be a candidate molecule for treating TNBC cells by targeting the AKT2 signaling pathway.
Keywords: Assay; cancer; Derivatives; Naphthoquinones; Plays

Transition metal complexes of Thiadiazole-Picolinic acid: Crystal structures, DFT insights and anticancer activity - Torambetov, Batirbay; Khojabaeva, Gulnaz; Bharty, M. K.; Gupta, Sushil K.; Kadirova, Shakhnoza; Pradeep, S.; Dastager, Syed G.; Gonnade, Rajesh G. (Journal of Molecular Structure, 2026)
Five novel transition metal complexes [Ni(H2aeth)2(Pic)2] (1), [Co(H2aeth)2(Pic)2] (2), [Ni(H2aeth)2(Pic)(HPic)] ClO4 (3), [Co(H2aeth)2(Pic)(HPic)]ClO4 (4) and [Zn(H2aeth)2 (Pic)(HPic)]ClO4 (5) were synthesized using a 2amino-5-ethylthio-1,3,4-thiadiazole (H2aeth) and picolinic acid (HPic) as co-ligands. These complexes were characterized by FT-IR, UV-Vis., X-ray photoelectron spectroscopy, TG-DTA, and single-crystal X-ray techniques. Crystallographic analysis confirmed distorted octahedral geometries around the metal centers with extensive hydrogen bonding networks promoting supramolecular assembly in the solid state. X-ray photoelectron spectroscopy (XPS), validated the +2 oxidation state of each metal center. Thermal studies indicated multistep decomposition processes resulting in the formation of metal oxides. Density functional theory (DFT) and timedependent DFT calculations were employed to explore electronic structures and predict UV-Vis. transitions, which showed good agreement with experimental data. Frontier molecular orbital (FMO) analysis revealed that Ni(II) complexes 1 and 3 are softer and more reactive, consistent with their observed biological activity. The anticancer potential of complexes 1-5 was evaluated in vitro using the MCF-7 human breast cancer cell line and the MTT assay. Complex 1 exhibited the strongest cytotoxicity (IC50 = 26.5 mu g/mL) followed by complexes 3 (34.9 mu g/mL), 4 (46.4 mu g/mL), 2 (81.1 mu g/mL), and 5 (103.3 mu g/mL). The observed activity trends correlate with metal identity and coordination environment, underlining the role of electronic and structural factors in modulating bioactivity. These findings suggest that thiadiazole-picolinate metal complexes, particularly those based on Ni (II), are promising scaffolds for anticancer drug development.
Keywords: Anti-cancer activity; crystal structure; DFT calculation; MCF-7 cell line; Picolinic acid; Thiadiazole complexes